2011
DOI: 10.1029/2010ja016258
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 150 km echoes linked with solar eclipse and their implications to the echoing phenomenon

Abstract: [1] This paper presents a study based on Gadanki radar observations of 150 km echoes made during the solar eclipse of 15 January 2010 that occurred during 1122-1515 IST. Radar echoes were observed only during 1150-1215 IST and 1344-1356 IST linked with the entry and recovery phases of the eclipse, respectively. The most striking observation found is the unusual ascending and descending features of the echoing regions observed during these two time periods. Although these echoes occurred at higher altitudes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…On the other hand, the lower echoing layer displays the necklace pattern that is similar to the solar zenith angle dependence of the F 1 layer height [ Kudeki and Fawcett , 1993]. Very recently, Patra et al [2011] have shown that such 150 km echoing pattern is closely related to the time evolution of F 1 layer density gradient. Thus the lower echoing layer can be attributed to the conventional 150 km echoes linked with the solar zenith angle dependence of the F 1 layer density gradients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, the lower echoing layer displays the necklace pattern that is similar to the solar zenith angle dependence of the F 1 layer height [ Kudeki and Fawcett , 1993]. Very recently, Patra et al [2011] have shown that such 150 km echoing pattern is closely related to the time evolution of F 1 layer density gradient. Thus the lower echoing layer can be attributed to the conventional 150 km echoes linked with the solar zenith angle dependence of the F 1 layer density gradients.…”
Section: Discussionmentioning
confidence: 97%
“… Tsunoda and Ecklund [2008] also invoked the involvement of metallic ions in the formation and transport of small plasma density structures. Patra et al [2011] have further argued that the daytime 150 km echoes and the nighttime echoes from the same height region displaying descending properties but with different vigor [ Patra and Rao , 2007b] are possibly of the same instability origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It explains the necklace shape because EUV photons penetrate most deeply at noon and less so at other times of the day as the photons have to travel through more atmosphere before encountering the same depth. It also explains why the echoes disappeared during the partial solar eclipse observed over the Gadanki radar site [ Patra et al , ] and why they were enhanced during a solar flare [ Reyes , ]. It may explain why they show the vertical structuring seen in Figure by invoking resonances which optimize this process at some altitudes and not others.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early observations made by the Jicamarca ISR in the 1960s, coherent scatter echoes have been observed from regions around 150 km altitude during daytime (Balsley, 1964). The origin of these echoes is still not understood since there are no obvious sources for plasma instabilities and, therefore, plasma irregularities in that region (Tsunoda and Ecklund, 2000;Patra et al, 2011).…”
Section: F S Rodrigues Et Al: Equatorial Vertical Drifts In Brazilmentioning
confidence: 99%